Bank dependence in emerging countries: Cross-border information percolation in mutual fund equity investing - Allen, Linda; Chakraborty, Suparna; Hazarika, Sonali; Su, Chih-Huei (Journal of International Business Studies, 2020)
In contrast to the literature involving U.S. bank domestic lending, we find that mutual funds affiliated with lending banks reduce their equity investment and turnover in the non-U.S.-listed stock of their non-U.S. borrowers compared to non-lending banks or unaffiliated mutual funds. Reduced equity holdings increase loan spreads, preserving the lending bank’s cross-border information monopoly. Equity market holdings and turnover are reduced when banks lend to firms in emerging nations and when the geographic distance between the lender and the mutual fund manager is greatest. Thereby, long-range information percolation may benefit global institutions at the expense of individual subsidiaries.